2019
DOI: 10.1073/pnas.1815823116
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of individual tubulin dimers binding to growing microtubules

Abstract: The biochemical basis of microtubule growth has remained elusive for over 30 years despite being fundamental for both cell division and associated chemotherapy strategies. Here, we combine interferometric scattering microscopy with recombinant tubulin to monitor individual tubulins binding to and dissociating from growing microtubule tips. We make direct, single-molecule measurements of tubulin association and dissociation rates. We detect two populations of transient dwell times and determine via binding-inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 59 publications
10
69
1
1
Order By: Relevance
“…We found that EB1 dwell time distributions on our disrupted structure microtubules were best modeled as two exponential distributions (Fig S2C,D), including one with a short dwell time (~20 ms), which could be associated with edge-bound EB1. In evaluating this dwell time relative to the kinetics of αβ-tubulin association, in 10 µM tubulin, it has been estimated that a free tubulin subunit would arrive to the growing end of the microtubule as rapidly as every ~2 ms , or as slowly as every ~10 ms (Mickolajczyk et al, 2019). Therefore, even the relatively short dwell times of edge-bounded EB1 molecules would be long enough to allow for multiple tubulin subunit arrivals while EB1 is bound to a protofilament edge.…”
Section: Discussionmentioning
confidence: 99%
“…We found that EB1 dwell time distributions on our disrupted structure microtubules were best modeled as two exponential distributions (Fig S2C,D), including one with a short dwell time (~20 ms), which could be associated with edge-bound EB1. In evaluating this dwell time relative to the kinetics of αβ-tubulin association, in 10 µM tubulin, it has been estimated that a free tubulin subunit would arrive to the growing end of the microtubule as rapidly as every ~2 ms , or as slowly as every ~10 ms (Mickolajczyk et al, 2019). Therefore, even the relatively short dwell times of edge-bounded EB1 molecules would be long enough to allow for multiple tubulin subunit arrivals while EB1 is bound to a protofilament edge.…”
Section: Discussionmentioning
confidence: 99%
“…We refined our prior algorithm (Ayaz et al , 2014; Piedra et al , 2016; Mickolajczyk et al , 2018) that used kinetic Monte Carlo (Gillespie, 1976; Gibson and Bruck, 2000) to simulate microtubule dynamics. The algorithm simulates one biochemical event (dimer association, dissociation, and GTP hydrolysis) at a time and therefore provides a ‘movie’ of microtubule dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we sought to investigate the consequences of incorporating various candidates for “missing state/biochemistry” into a computational model, with the aim of better predicting the concentration-dependence of catastrophe. We elaborated a Monte Carlo-based algorithm developed in the lab (Ayaz et al , 2014; Piedra et al , 2016; Mickolajczyk et al , 2018) to test if incorporating a GDP.P i state or long-range coupling (reflecting conformational accommodation) improved predictions of microtubule catastrophe. We incorporated the GDP.P i state and conformational coupling separately for simplicity and to be able to assess the effect of each change in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ATP motility buffer was introduced and incubated for 5 min to initiate movement, the flow cell was then transferred to the microscope. The iSCAT microscope used in the work was described previously 34 . Images were taken using custom written LabVIEW software.…”
Section: Methodsmentioning
confidence: 99%